Investigation of the properties of encapsulated hydrophilic and hydrophobic drugs in whey protein microparticles - ULAĞ, SONGÜL; GÜNDÜZ, OĞUZHAN (My University, 2022)
© 2022 Elsevier B.V.In this study, the amoxicillin (AMX) and rifampicin (RIF) were loaded into the whey protein (WP) to form the hydrophilic and hydrophobic drugs loaded whey protein microparticles. Scanning electron microscopy (SEM) images demonstrated that AMX addition increased the particle size, but RIF addition decreased the dimensions of the particles. The Fourier-transformed infrared spectroscopy (FTIR) results showed that both drugs were successfully loaded into the protein. AMX and RIF were ultimately released from the WP microparticles after 1440 min, according to the drug release test. Two drugs exhibited the same behaviour, but in the first hour, AMX had more release than the RIF.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Tarım Bilimleri; Mühendislik; Doğa Bilimleri Genel; TARIM, MULTİDİSİPLİNLER; MÜHENDİSLİK, MEKANİK; ÇOK DİSİPLİNLİ BİLİMLER; FİZİK, YOĞUN MADDE; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); AGRICULTURAL SCIENCES; ENGINEERING; NATURAL SCIENCES, GENERAL; PHYSICS; AGRICULTURE, MULTIDISCIPLINARY; ENGINEERING, MECHANICAL; MULTIDISCIPLINARY SCIENCES; PHYSICS, CONDENSED MATTER; Yoğun Madde Fiziği; Elektronik, Optik ve Manyetik Malzemeler; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Tarım ve Biyoloji Bilimleri (çeşitli); Multidisipliner; Fizik Bilimleri; Yaşam Bilimleri; Condensed Matter Physics; Electronic, Optical and Magnetic Materials; Mechanical Engineering; Computational Mechanics; Automotive Engineering; Agricultural and Biological Sciences (miscellaneous); Multidisciplinary; Physical Sciences; Life Sciences; Amoxicillin; Biomaterials; Electrospray; FTIR; Rifampicin; Whey protein; DELIVERY